Abusive supervisors and employee work-to-family conflict in Chinese construction projects: how does family support help?. Issue 12 (1st December 2020) - Ju, Lei; Zhao, Wanyu; Wu, Chunlin; Li, Haofan; Ning, Xin
Abstract: Work to family conflict (WFC) experienced by employees working in the construction industry has received significant attention from researchers. However, workplace bullying and incivility are rarely considered in relation to WFC, and even more rarely in the context of Chinese construction. Consequently, this study aims to examine how abusive supervisors can influence WFC for employees. Through two surveys of Chinese construction workers, this study analyses the mediation effect of employee psychological distress, and the moderation mechanism of employee family support on the relationship between abusive supervision and employee WFC. The findings show that abusive supervision is positively related to employee WFC, and employees' psychological distress mediates this relationship significantly. Employee family support moderates the direct and indirect relationship between abusive supervision and employee WFC. Understanding how abusive supervision influences employee WFC is useful for both its theoretical and practical implications, particularly in effectively relieving employee work pressure, reducing the transfer of individual stress into the family domain, promoting employee well-being, and improving construction project performance.